Identification of the causative agent of cutaneous leishmaniasis in Chichaoua province, Morocco - Rhajaoui M.; Sebti F.; Fellah H.; Alam M.Z.; Nasereddin A.; Abbasi I.; Schönian G. (Parasite, 2012)
Cutaneous leishmaniasis (CL) in Morocco is caused by three species, Leishmania major, L. tropica and L. infantum. CL has been known in Chichaoua province since 2000. Using DNA extracted from microscopic slides and parasite cultures, collected in the years 2006 and 2009, we identified for the first time L. tropica as the causative agent of CL in this region. Species identification was achieved by performing the ITS1-PCR-RFLP approach. By using this method it was possible to identify parasites in Giemsa stained slides containing less than five parasites per oil-immersion field even they were conserved for up to four months.